2008
DOI: 10.1152/japplphysiol.00463.2006
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1and TNF-α are involved in the transcription of type I collagen α2gene in soleus muscle atrophied by mechanical unloading

Abstract: The aim of this study was to examine the effect of hindlimb suspension (HS) on the expressions of COL1A2 (type I collagen alpha(2) chain) mRNA and its regulatory factors, transforming growth factors (TGF)-beta(1), -beta(2), and -beta(3), phosphorylated Smad3, and tumor necrosis factor-alpha (TNF-alpha) in rat hindlimb muscles. Forty-eight male Wistar rats (age, 5 wk) were randomly assigned to HS for 1, 3, 7, and 14 days and control (n = 6 for each). During the exposure to HS, COL1A2 mRNA expression decreased i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
35
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 31 publications
8
35
1
Order By: Relevance
“…The changes in IL-6 mRNA expression followed a similar pattern to those of TNF-α mRNA, but did not reach significance until 21 days of immobilization. Although a previous study denied a major role for TNF-α in muscle disuse atrophy, except under cachexic conditions (15), our observation in the soleus muscle was consistent with other recently reported studies using hindlimb suspension (1,14), hindlimb immobilization (7,18), and denervation (27), as experimental models. However, in our previous study, MAFbx/ atrogin-1 and MuRF1 mRNA levels in the soleus muscle peaked after 3 days (6.3-fold), declined at 7 days (4.7-fold) and 14 days (2.0-fold), and then reterior muscles after 21 days of immobilization when no change in active phosphorylated Akt was observed in the immobilized muscles (24).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The changes in IL-6 mRNA expression followed a similar pattern to those of TNF-α mRNA, but did not reach significance until 21 days of immobilization. Although a previous study denied a major role for TNF-α in muscle disuse atrophy, except under cachexic conditions (15), our observation in the soleus muscle was consistent with other recently reported studies using hindlimb suspension (1,14), hindlimb immobilization (7,18), and denervation (27), as experimental models. However, in our previous study, MAFbx/ atrogin-1 and MuRF1 mRNA levels in the soleus muscle peaked after 3 days (6.3-fold), declined at 7 days (4.7-fold) and 14 days (2.0-fold), and then reterior muscles after 21 days of immobilization when no change in active phosphorylated Akt was observed in the immobilized muscles (24).…”
Section: Discussionsupporting
confidence: 93%
“…Muscle-specific overexpression of FOXO1 or FOXO3a is sufficient to cause skeletal muscle atrophy in vivo (17,36). Studies using inactivity-induced atrophy models also report that 14), hindlimb immobilization (7,18), and denervation (27). Kim et al (19) reported that mRNA levels of inflammatory cytokines increased in the mixed fiber-type gastrocnemius muscle after 14 days of cast immobilization.…”
mentioning
confidence: 99%
“…Overall, body weight during HU was smaller than that of C (aged-matched at 14 days). Indeed, a significant body weight decrease is generally observed during the first week of HU, but thereafter the growing showed the same time course of C rats (13,16).…”
Section: Resultsmentioning
confidence: 87%
“…Furthermore, immobilization using different techniques is associated with transient alterations of the canonical (15) and noncanonical TGF-β signaling pathways (19, 38). We therefore evaluated whether losartan would have beneficial effects on skeletal muscle of 21-month-old mice subjected to immobilization of the TA muscle for 21 days using a surgical staple procedure (39).…”
Section: Resultsmentioning
confidence: 99%